2021
DOI: 10.1002/jeq2.20264
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics interaction with terrestrial plants and their impacts on agriculture

Abstract: Microplastics (MPs) are widespread in natural ecosystems and have attracted considerable attention from scientists all over the world because they are believed to threaten every life form. In addition to their potential physical and chemical effects on organisms, MPs may act as a carrier for many micropollutants, including antibiotics, heavy metals, and others. Over the last 10-15 yr, extensive research has been carried out on MPs in marine environments regarding their sources, fate, and toxicity.However, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 125 publications
0
12
0
1
Order By: Relevance
“…Microplastics is easily penetrate through seeds, roots, stems, leaves, fruits and plant cells because of their size and type under controlled conditions the uptake of microplastics has been reported. MPs can pass through plant cell walls and membrane barriers, obstruct cell pores and cause cell death that can be reported by Raza Ullah et al (2021). Li et al (2019) had reported polystyrene MPs can be transfer and accumulated in the roots of raw vegetables and transmitted from root to shoot tissues.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Microplastics is easily penetrate through seeds, roots, stems, leaves, fruits and plant cells because of their size and type under controlled conditions the uptake of microplastics has been reported. MPs can pass through plant cell walls and membrane barriers, obstruct cell pores and cause cell death that can be reported by Raza Ullah et al (2021). Li et al (2019) had reported polystyrene MPs can be transfer and accumulated in the roots of raw vegetables and transmitted from root to shoot tissues.…”
Section: Discussionmentioning
confidence: 90%
“…While, pesticides, herbicides and fertilizers are the main sources of microplastics accumulation in plant and soil was reported in Raza Ullah et al (2021). Pietra et al (2019) reported microplastics were present in mineral fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Karl Ziegler and Giulio Natta won the Nobel Prize in Chemistry 1963 for their discoveries in the field of the chemistry of high polymers. Although highly beneficial, in the last few decades plastic debris and microplastic have become widespread in the ocean, farmlands, table salt, and drinking water, to name a few (Ullah et al., 2021; Yu et al., 2018; Zhang et al., 2020). In addition, there are many emerging contaminants such as PFAS, PPCPs, polychlorinated biphenyl, and nanomaterials that have been introduced and already reached dangerous levels in the environments (Boxall et al., 2012; Crone et al., 2019; Zhao et al., 2021).…”
Section: Pollutions From Science and Technology Advancementsmentioning
confidence: 99%
“…Plastics dumped into the environment are converted into microplastics (MPs) by thermal decomposition, physical wear, exposure to ultraviolet radiation, and wind. 1 MPs, generally defined as plastics <5 mm in size, have been a global problem of growing concern. Because of their ubiquitity, size, source, chemical composition, and many interactions with biological and abiotic factors in all ecosystems, microplastics exact several direct and indirect impacts on the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Plastics dumped into the environment are converted into microplastics (MPs) by thermal decomposition, physical wear, exposure to ultraviolet radiation, and wind . MPs, generally defined as plastics <5 mm in size, have been a global problem of growing concern.…”
Section: Introductionmentioning
confidence: 99%